Soil Processes and Current Trends in Quality Assessment - Hernandez Soriano, Maria C. (IntechOpen, 2013)
Natural processes and human activities alter the properties and quality of soils over time. Nowadays, the growing interest in soil protection prompts abundant research to estimate soil quality in wide-ranging environmental scenarios. The assessment of soil quality entails the evaluation of the capability of a soil to perform its functions in present scenarios but also how those functions can be preserved for future land use. Currently, soil processes, physical, chemical, and biological properties are recognized as indicators to estimate soil quality. Soil processes and current trends in quality assessment provides a wide depiction of current research conducted in soil quality assessment, encompassing general studies on soil processes, evaluation of significant indicators of soil quality such as soil organic matter dynamic and soil-plant interaction, while presenting diverse strategies for soil fitness amelioration.